China's Wild West - Pontikos, Urszula (United Kingdom : Riley, Michael, 2008)
Every winter the Yurungkash river in western China dries up, revealing an expanse of river-worn stones. There, hidden within the rock, lies a treasure forty times more valuable than gold - jade. Hundreds of people gather in the riverbeds, endlessly scrabbling at rocks in search of a jewel they might not find. During the winter months, the local Muslim minority Uyghur turns from farming to digging to supplement their income. Though their chances of improving their condition are slim, people remain hopeful.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films